Disease environment and civil conflicts - Matteo Cervellati; Uwe Sunde; Simona Valmori (Institute for the Study of Labor (IZA), 2011)
This paper tests the hypothesis that a high and persistent exposure to infectious diseases increases the likelihood of civil conflicts. Diseases that are difficult to prevent and treat may reduce the opportunity costs of violent activities, both directly and indirectly. The analysis exploits new data on the number of multi-host vector-transmitted infectious diseases that are endemic in each country. As consequence of their specific features, the presence of these pathogens in a country is closely related to geo-climatological conditions and exogenous to civil conflict. The findings document that a larger disease richness is a statistically robust and quantitatively relevant determinant of civil conflicts for the period 1960-2004. Exploiting within country variation, the findings also document that interactions between climatological shocks in terms of droughts and the disease environment have a significant effect on the risk of civil wars. The results are robust to different specifications, data sets and estimation methods, and suggest that the persistent exposure to a more unfavorable environment in terms of disease richness is an important determinant of the incidence of civil conflict. The results also suggest the potential relevance of a channel linking geography to economic development that has not been investigated in the literature.
urn:nbn:de:101:1-201104134558
Keywords: D74; J1; 330; disease environment; civil conflict; multi-host vector-transmitted pathogens; civil war; Infektionskrankheit; Klima; Geographie; Bürgerkrieg; Entwicklung; Schätzung; Entwicklungsländer